Big Data in civil engineering: a state-of-the-art survey. Issue 4 (1st October 2016) - Kapliński, Oleg; Košeleva, Natalija; Ropaitė, Guoda
Abstract: Data generation has increased drastically over the past few years. Data management has also grown in importance because extracting the significant value out of a huge pile of raw data is of prime importance while making different decisions. This article reviews the concept of Big Data. The Thomson Reuters Web of Science Core Collection academic database was used to overview publications that contained "BIG DATA" keywords and were included in Web of Science Category under "Engineering". The analysis of publications was made according to year, country, journal, authors, language and funding agency.